How Machiavellianism, Psychopathy, and Narcissism Affect Sustainable Entrepreneurial Orientation: The Moderating Effect of Psychological Resilience - Wu, Wenqing; Wang, Hongxin; Lee, Hsiu-Yu; Lin, Yu-Ting; Guo, Feng (Frontiers in Psychology, 2019)
In order to solve increasingly serious environmental problems, sustainable entrepreneurship based on the concept of sustainable development has gradually attracted attention and discussion in the academic field. Moreover, it is of great significance to analyze the influence of personality on entrepreneurial orientation considering dark and bright personality traits. On the basis of existing research, we analyzed the relationships between the three elements of the dark triad (Machiavellianism, psychopathy, and narcissism), psychological resilience, and sustainable entrepreneurial orientation (SEO) through a questionnaire survey. Results involve data from 328 MBA students in Tianjin University of China. The results showed that Machiavellianism and psychopathy negatively affected SEO, and narcissism positively affected SEO; psychological resilience and SEO had a significant positive association; and psychological resilience had a moderating effect on the relationship between the three elements of the dark triad and SEO. Our research has reference value and its findings have important implications for entrepreneurship research and education.